PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI KANTOR KECAMATAN BOGOR TIMUR - Ilyas, Yasnimar; Telaumbanua, Indarti (Economicus, 2021)
The purpose of this study was to determine the effect of transformational leadership style and organizational culture partially and simultaneously on organizational commitment in the office of East Bogor District, Bogor Regency. This type of research is quantitative causality. The research location is the East Bogor District Office, Bogor Regency. The results showed (1). There is an influence and significance of transformational leadership on organizational commitment. This is evidenced by the value of t count = 29.040> t table 2.119 with a significance value of 0.000> 0.05. (2). There is no positive and significant influence of organizational culture on organizational commitment. This is evidenced by the value of t count = -1.634 <t table 2.119 with a significance value of 0.122 <0.05. (3). The simultaneous hypothesis test results show that together the transformational leadership and organizational culture variables have a positive and significant influence on organizational commitment. This is evidenced by the calculated F value 2806.727> F table 3.63. (4). The variable that most dominantly affects organizational commitment is the variable of transformational leadership, this can be seen from the regression coefficient value of the transformational leadership variable of 0.965.